(3GdeMH hGdeMHhH hGdeThe hGdeTQhHs - (3GdnqSpQqj Hf CMeO Hf GdSQj GdcfOj, CHh GdMSf GdnqQnqaGA,J (B366 (3g` s
(3ChdgG (B:s
(3hHYO, abO SCdfj ef eNGdaJg dGnJSJWGY, hMbg Cf ojLGH hjWGY, Cf CLeY dg cJGHkG MGhjkG s
(3BNQgG (B:s
(3ef RLd dWja dceGd GdOjf GHf GdfHjg(B: (3RYbJ MQGe RhLj hGdfHj ZOG jWdb Je cJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B208s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B15 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1611s
Keywords: (3GdCOHs